2020
DOI: 10.1186/s12909-020-1939-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative value of a simulation by gaming and a traditional teaching method to improve clinical reasoning skills necessary to detect patient deterioration: a randomized study in nursing students

Abstract: Background: Early detection and response to patient deterioration influence patient prognosis. Nursing education is therefore essential. The objective of this randomized controlled trial was to compare the respective educational value of simulation by gaming (SG) and a traditional teaching (TT) method to improve clinical reasoning (CR) skills necessary to detect patient deterioration.Methods: In a prospective multicenter study, and after consent, 2nd year nursing students were randomized into two groups:-Simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
47
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 50 publications
(117 reference statements)
8
47
0
8
Order By: Relevance
“…6 In recent years, serious games have been recognized as a potential tool for enhancing medical education. [7][8][9] The merit of educational games, such as interactivity, simulation, and immediate feedback, make such games very effective, 6 particularly in circumstances such as during the COVID-19 pandemic, when online instruction is a good alternative. Previous researchers have revealed the effect of serious games or games designed for a particular educational purpose.…”
Section: Introductionmentioning
confidence: 99%
“…6 In recent years, serious games have been recognized as a potential tool for enhancing medical education. [7][8][9] The merit of educational games, such as interactivity, simulation, and immediate feedback, make such games very effective, 6 particularly in circumstances such as during the COVID-19 pandemic, when online instruction is a good alternative. Previous researchers have revealed the effect of serious games or games designed for a particular educational purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Such work is of great interest given the growing number of platforms using virtual humans as a therapeutic tool for clinical populations with social cognition deficits 11 , or in serious games to improve clinical reasoning skills in healthcare professionals 12 15 . For instance, by improving a virtual character’s anthropomorphism, a higher affective reaction may be elicited towards its pain, which may be desirable in order to train healthcare professionals in emotional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to be an effective teaching method, compared to traditional methods used in pharmacy [ 12 ]. In particular, studies showed that students gain self-confidence [ 23 , 24 ], are motivated to learn [ 25 ], and improve their professional skills [ 24 ] when simulation methods are used. Students liked the method and were satisfied with the teaching [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, studies showed that students gain self-confidence [ 23 , 24 ], are motivated to learn [ 25 ], and improve their professional skills [ 24 ] when simulation methods are used. Students liked the method and were satisfied with the teaching [ 25 ]. Simulation methods can be combined with a serious game [ 26 ].…”
Section: Introductionmentioning
confidence: 99%